The Terraforming of Mars as an interdisciplinary subject to approach scientific knowledge in High School (Research, Society and Development, 2019)
The present text aims to present a proposal of didactic activities of an interdisciplinary nature for high school, having as its guiding principle the use of an exciting topic, in the case of terraforming de Marte. The research starts from the discussion of interdisciplinarity and as a result presents a bibliography study that made possible to form the didactic proposal, which is the main aspect of the text. The didactic proposal is guided by questionings and debates around the possibility of creating in Mars the life conditions of Earth, so it’s possible to live in the planet: Can we terraform Mars? What is necessary for that? How would the adjustment of life be in Mars? From these questions, discussions referring to interdisciplinary topics that can be approached in the classroom are indicated. The essay ends pointing out the validity of this kind of activity, especially when it’s about themes of the students’ interests, and it emphasizes that a specific discipline would be able to answer these questions, which acknowledge the necessity of interdisciplinary education.